Pengetahuan Ibu Hamil Tentang HIV/AIDS di Puskesmas Haurgeulis Kabupaten Indramayu - Umroh Umroh; M Saefulloh; Dian Fitriyani (Jurnal Medika Cendikia, 2015)
HIV or Human Immunodeficiency Virus is Virus that attack of white blood cells(limfosit) in the body resulting decline in the human immune. AIDS caused by a virus HIV. The purpose of this study is to determine the knowledge of pregnant mother about HIV/AIDS at Haurgeulis Public Health Centre, Indramayu Regency Year 2014. This research is a descriptive study. Study population was 65 pregnant motherHaurgeulisin Public Health Centre, Indramayu Regency year 2014 and the sample was using the accidental sampling. The research instrument was used a questionnaire with total of questionare 30 questions. Based on research result shows that pregnant mother knowledge about HIV/AIDS is (20,01%) of the respondents have less knowledge while (70,76%) of respondents have sufficient knowledge and (9,23%) of the respondents have a good knowledge. A total of (46,15%) of respondents have a sufficient knowledge about the understanding of HIV/AIDS, as many (55,38%) of the respondents have a sufficient knowledge about sign and symptoms of HIV/AIDS, as many (41,53%) of the respondents have sufficient of HIV/AIDS and as many (49,23%) of the respondents have a transmission knowledge about the of HIV/AIDS. Have sufficient knowledge about the prevention 49,24%. The conclusion of this research is the knowledge of pregnant mother about HIV/AIDS is in the category of sufficient knowledge. It is expected that health services can increase the information media and education through counseling and health reproductive education to prevent the spread of viruses HIV/AIDS.